Effects of Biomate® inoculant and dextrose on the fermentation of alfalfa silages - Lin, C.; Bolsen, K.K.; Bradford, J.E.; Brent, B.E.; Feyerherm, A.M.; Aimutis, W.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study documented once again that ensiling alfalfa is difficult and unpredictable. Adding 2% dextrose or Biomate® inoculant alone or in combination had little influence on the ensiling process but did improve fermentation efficiency somewhat. The pre-ensiling characteristics (i.e., dry matter (DM) and water soluble carbohydrate (WSC) values, buffering capacity, and epiphytic microflora) at the different cuttings and stages of maturity undoubtedly influenced the effectiveness of the two additives. Apparently, alfalfa often has too little WSC and too much buffering capacity to produce adequately preserved silage, especially when ensiled at a low DM content (less than 30 to 34%).
Keywords: Beef; Silage; Alfalfa; Bacterial; Inoculant; Dextrose